NEGATIVE EFFECTS OF PESTICIDES ON THE ENVIRONMENT AND THE FARMERS AWARENESS IN SAUDI ARABIA: A CASE STUDY - A. A. Al-Zaidi; E. A. Elhag; S. H. Al-Otaibi; M. B. Baig (Journal of Animal and Plant Sciences, 2011)
The main goal of this study was to determine the levels of knowledge of the farmers on the effect of pesticides on environment in Dawadmi Province, Saudi Arabia. This is achieved through realizing some secondary objectives such as identification of the farmers' socioeconomic characteristics and its relation to some of the study variables, their attitude towards the negative effects of pesticides on the environment, their knowledge level about pesticides effect and their sources of information about pesticides use, storage and disposal. The study covered (6) locations/areas, and some 204 farmers were included as stratified random sample. The results revealed that the 5% farmers do not rely on agricultural extension but they seek information from other trustworthy sources. The farmers have a positive attitude towards learning about the negative effects of the pesticides on the environment. The study also showed that the most common method of pesticides application is spraying using axi-sprayers or portable sprayers. The results of the study establish the need for the launching of extension programs on the proper and safe methods for pesticides handling and application. The study also suggests the need for improving the existing agricultural extension service to make positive contributions to production and ensure the health of the farmers/farm workers while keeping the environment safe and clean. Also there is a communication gap between the farmers and research centers as observed in the study. Extension programs, brochures and field visits are the sources of information that farmers rely on. Farmers should be enlightened about the importance of the frequent and regular medical checking up of their workers and especially those dealing with the agricultural chemicals.
Keywords: Sustainable Agriculture; Awareness; Clean Environment; Efficient Extension; Handling Pesticides.